2018
DOI: 10.1080/14767058.2018.1489531
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of on-admission factors on attainment of therapeutic serum concentrations of magnesium sulfate in women treated for a diagnosis of preeclampsia

Abstract: On-admission factors, especially BMI and renal clearance indices, of women with PE may affect timely attainment of therapeutic serum magnesium levels. Validation of its clinical impact requires further study focusing on women with severe PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
2
13
2
2
Order By: Relevance
“…The association between elevated BMI and sub-therapeutic MgSO 4 levels was not con rmed in our research, which was inconsistent with previous reports [16,27,28] . The reason may be related to the small sample of cases, which lead to the weakening of statistical signi cance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The association between elevated BMI and sub-therapeutic MgSO 4 levels was not con rmed in our research, which was inconsistent with previous reports [16,27,28] . The reason may be related to the small sample of cases, which lead to the weakening of statistical signi cance.…”
Section: Discussioncontrasting
confidence: 99%
“…The elimination of MgSO 4 occurs primarily in the kidney, and PE associated renal damage can result in increased serum magnesium levels [16] . A previous publication showed that the glomerular ltration rate of normal pregnant women was 149 mL/min/1.73 m 2 body surface area [17] .We used Ccr to estimate the glomerular ltration rate, which was calculated by the Cockcroft-Gault equation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of MgSO 4 occurs primarily in the kidney, and PE associated renal damage can result in increased serum magnesium levels [12] . A previous publication showed that the glomerular filtration rate of normal pregnant women was 149 mL/min/1.73 m 2 body surface area [13] .We used Ccr to estimate the glomerular filtration rate, which was calculated by the Our study further found that when maternal Ccr ≥ 132.82 mL/min, the blood magnesium concentration of severe preeclampisa patients was less likely to reach the target range.…”
Section: Discussionmentioning
confidence: 99%
“…However, a pharmacodynamics study showed that with IV 4 g loading and 2 g/h maintenance dose, blood magnesium concentration was twice the baseline value within 30 minutes, and plateaued at 2-4 hours with minimum fluctuation [8,14,15] . At 2 hours after administration, serum magnesium ranged broadly from 1.0-3.5 mmol/L [12] . With our MgSO 4 IV infusion regimen (5 g loading dose and 1.5 g/h maintained for 10 hours, or no loading dose and 1.5 g/h maintained for 10 hours), our data suggested that for the duration of MgSO 4 maintenance dose of more than 2.375 hours, the blood magnesium concentration was more likely to reach the target range of…”
Section: Discussionmentioning
confidence: 99%